The Evolution, Principles, Practices and Development of Corporate Governance in Nigeria - Ishola, Oluwadamilola (2015)
This research study critically examines the corporate governance structure in the Anglo-American countries and in comparison with corporate governance provisions and implementation structures available in Nigeria. It highlights Nigeria's current position in corporate governance matters such as disclosures, enforcement,board composition, qualification and appointment, board diversity, and political interference.